2022
DOI: 10.23960/jhptt.222116-125
|View full text |Cite
|
Sign up to set email alerts
|

Potency of two Trichoderma harzianum isolates in liquid and solid organic formula for controlling bacterial wilt on tomato in the field

Abstract: This research aimed to determine the potency of two Trichoderma harzianum isolates in solid and liquid organic formulas to control bacterial wilt and on growth and yield of tomato in the field. This research was carried out at the Laboratory of Plant Protection and the tomato field at Banteran Village, Sumbang Sub-District, Banyumas Regency at altitude of 600 m above sea level for four months. A randomized block design was used with five replicates. The treatments were control, T. harzianum T10, T. harzianum T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the present study, the open field trials under natural infection of early blight revealed that the CFs of these Trichoderma strains not only mitigated the infection of the pathogen but also escalated the yield production, which epitomizes the positive effect of CFs and their capability to promote fruit production in open field conditions even during natural infection. A study by Soesanto et al (2022) documented that the culture filtrates of T. harzianum not only improved the growth and yield components of tomato plants but also increased the phenolic compounds, number of fruits, and total yield under in vivo conditions (Soesanto et al, 2022). In another study, a significant increase in yield and growth-related parameters of Celosia cristata was recorded after the inoculation of Trichoderma strains .…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the open field trials under natural infection of early blight revealed that the CFs of these Trichoderma strains not only mitigated the infection of the pathogen but also escalated the yield production, which epitomizes the positive effect of CFs and their capability to promote fruit production in open field conditions even during natural infection. A study by Soesanto et al (2022) documented that the culture filtrates of T. harzianum not only improved the growth and yield components of tomato plants but also increased the phenolic compounds, number of fruits, and total yield under in vivo conditions (Soesanto et al, 2022). In another study, a significant increase in yield and growth-related parameters of Celosia cristata was recorded after the inoculation of Trichoderma strains .…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the open field trials under natural infection of early blight revealed that the CFs of these Trichoderma strains not only mitigated the infection of the pathogen but also escalated the yield production, which epitomizes the positive effect of CFs and their capability to promote fruit production in open field conditions even during natural infection. A study by Soesanto et al. (2022) documented that the culture filtrates of T. harzianum not only improved the growth and yield components of tomato plants but also increased the phenolic compounds, number of fruits, and total yield under in vivo conditions ( Soesanto et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Soesanto et al. (2022) documented that the culture filtrates of T. harzianum not only improved the growth and yield components of tomato plants but also increased the phenolic compounds, number of fruits, and total yield under in vivo conditions ( Soesanto et al., 2022 ). In another study, a significant increase in yield and growth-related parameters of Celosia cristata was recorded after the inoculation of Trichoderma strains (Wang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%